Ergonomics risk assessment in musculoskeletal disorders among plantation workers in Selangor agricultural development corporation, Sg Tengi Selatan, Kuala Kubu Bahru, Selangor, Malaysia: article - Mohamad Shafri, Mohamad Shahidan (2021)
A cross-sectional study evaluated repetitive motion on ergonomics working conditions and the occurrence of self-reported musculoskeletal symptoms among 50 plantation workers. A questionnaire, guided checklist from Department of Occupational Safety and Health Malaysia and Work-Ergonomics Risk Assessment (WERA) method were used. Descriptive statistics and multivariable analyses were used to characterize the data and identify factors associated with work-related musculoskeletal disorders. The results showed that a high prevalence of musculoskeletal symptoms, particularly neck, shoulder, and upper back were impacted by socio-demographics and job characteristics such as age, BMI, overall work experience, and normal working hours. Chi-square test indicated wrist, back and neck were frequently imposed repetitive motion yielding 9.78 (0.008), 22.68 (0.01), 6.70 (0.04), 6.09 (0.04) and 12.47 (0.002). These results emphasize the need for ergonomics intervention or measures aid to improve the working conditions of this population.